A) Có \(f\left(x\right)=3x^2-2x-1\)
\(\Rightarrow f\left(1\right)=3.1^2-2.1-1\)
\(f\left(1\right)=3-2-1=0\)
\(\Rightarrow f\left(-\frac{1}{3}\right)=3.\left(-\frac{1}{3}\right)^2-2.\frac{1}{3}-1\)
\(f\left(-\frac{1}{3}\right)=3.\frac{1}{9}-\frac{2}{3}-1\)
\(f\left(-\frac{1}{3}\right)=\frac{1}{3}-\frac{2}{3}-1=-\frac{4}{3}\)
Có \(f\left(x\right)=3x^2-2x-1\)
Để \(f\left(x\right)=0\)
Thì \(3x^2-2x-1=0\)
\(\Rightarrow x\left(3x-2\right)-1=0\)
\(\Rightarrow x\left(3x-2\right)=1\)
TH1 : \(\hept{\begin{cases}x=1\\3x-2=1\end{cases}\Rightarrow\hept{\begin{cases}x=1\\x=1\end{cases}}}\)
TH2 : \(\hept{\begin{cases}x=-1\\3x-2=-1\end{cases}\Rightarrow}\hept{\begin{cases}x=-1\\x=\frac{1}{3}\end{cases}}\)( loại )
Vậy x=1 thì f(x) = 0
A, ta có f(x) =3x2-2x-1
=> f(1)=3.12-2.1-1=3-2-1=0
\(f\left(\frac{-1}{3}\right)=3.\left(-\frac{1}{3}\right)^2-2.\left(-\frac{1}{3}\right)-1\)
= \(\frac{1}{3}+\frac{2}{3}-1=1-1=0\)
B, theo a ta có \(f\left(1\right)=f\left(\frac{-1}{3}\right)=0\)
Vậy x=1 và x=\(\frac{-1}{3}\)thì đa thức f(x)=0
tk mk nha bạn ,mk xong đầu tiên
*****Chúc bạn học giỏi*****